Enhanced localized superconductivity in Sr2RuO4 thin film by pulsed laser deposition. (21st July 2016) - Cao, J; Massarotti, D; Vickers, M E; Kursumovic, A; Di Bernardo, A; Robinson, J W A; Tafuri, F; MacManus-Driscoll, J L; Blamire, M G
Abstract: Superconducting c -axis-oriented Sr2 RuO4 thin film has been fabricated using pulsed laser deposition. Although the superconductivity is localized, the onset critical temperature is enhanced over the bulk value. X-ray microstructural analysis of Sr2 RuO4 superconducting and non-superconducting thin films suggests the existence of the localized stacking faults and an overall c -axis lattice expansion which may account for the locally enhanced superconductivity.